Overview of Healthcare Workers' Preparedness in Disaster Management at Cut Meutia Regional General Hospital, North Aceh Regency - Faiq Ghosan Alghoniy Albin; Maulina Debbyousha; Cut Khairunnisa; Nur Fardian; Noviana Zara; Ridhalul Ikhsan (Faculty of Medicine University of Malikussaleh, 2024)
Disaster management involves a series of activities, including prevention, risk mitigation, rescue, rehabilitation, and reconstruction, carried out before, during, and after a disaster occurs. The goal is to avoid or reduce the impact of disasters. In this context, the role of healthcare workers is crucial in disaster response. In Indonesia, there are regulations that mandate the responsibility of every healthcare worker in disaster management. To date, there has been no research or report describing the readiness of healthcare workers at RSUD Cut Meutia regarding disaster management. This study aims to provide an overview of the extent of healthcare workers' readiness in managing disasters at RSUD Cut Meutia in North Aceh Regency. This research is descriptive with a cross-sectional design, involving 285 respondents, and using Stratified Random Sampling technique. The research findings indicate that the majority of respondents have good knowledge of disaster management (52.3%), with a small percentage having a lack of understanding (2.1%). Most respondents show a positive attitude towards disaster management efforts (95.4%). Meanwhile, in terms of practices or previous experiences, the majority of respondents have adequate understanding (44.6%). The conclusion of this study is that the readiness of healthcare workers at RSUD Cut Meutia in North Aceh Regency in disaster management can generally be categorized as good.